Obituary for Tamara Grummt - Braunbeck, Thomas; Erdinger, Lothar; Frimmel, Fritz H.; Hollert, Henner; Knasmüller, Siegfried; DeMarini, David M.; Plewa, Michael J.; Richardson, Susan D.; Triebskorn, Rita; de Aragão Umbuzeiro, Gisela; White, Paul A. (Environmental sciences Europe, 2020)
Tamara Grummt passed away on January 26, 2020 in Oelsnitz/Vogtland, Germany. Tamara was one of the scientific pioneers in the field of environmental toxicology, namely genotoxicity and hygiene of drinking and bathing waters. Her passing is not only a great loss to environmental research and to the global environmental toxicology community—we have lost an outstanding personality with the heart in the right place, who has become, for many of us, a wonderful friend.
Gesehen am 18.05.2020